THE IMPACT OF INVENTORY MANAGEMENT ON COMPANIES - de Pani, Jeferson Arco; Reis Filho, Ramilio Ramalho (Revista Interface Tecnológica, 2023)
Inventory Control is part of the day-to-day of companies and it is a subject that has several works published on the subject due to its importance and necessity. Inventory management can be considered as a set of tasks, techniques and methodologies whose function is to meet the needs of the company. Inventory management is essential for the existence of all companies. The objective of this research is to analyze the impact of inventory management within companies through a systematic review of the literature. Through the in-depth study of articles, stock management in companies was demonstrated in a practical way, demonstrating the positive and negative impacts. At the end of the research, we can conclude that inventory management is very important and causes great impacts on the company as a whole.
Keywords: Stock Management; Impacts of Inventory Management